(untitled) (Plant Tissue Culture and Biotechnology, 2010)
This long term study demonstrates for the first time that it is possible to propagate embryogenic Vigna trilobata and to subsequently initiate the differentiation of embryos into complete plantlets. Initiation of callus was possible on 2,4-D. Somatic embryos differentiated on modified MS basal nutrient medium with 1.0 mg/l of 2,4-D and 0.5 mg/l of Kn. Sustained cell division resulted in globular and heart shape stages of somatic embryos. Transfer of embryos on to a fresh modified MS basal medium with 0.5 mg/l of Kn and 0.5 mg/l of GA3 helped them to attain maturation and germination. However, the propagation of cells, as well as the differentiation of embryos, were inhibited by a continuous application of these growth regulators. For this reason, a long period on medium lacking these growth regulators was necessary before the differentiation of embryos occurred again. The consequences for improving the propagation of embryogenic cultures in Vigna species are discussed. Key words: Pasture legume, Vigna trilobata, Globular, Heart shape, somatic embryogenesis D.O.I. 10.3329/ptcb.v19i1.4990 Plant Tissue Cult. & Biotech. 19(1): 89-99, 2009 (June)